Analisis Beban Kerja Perawat Berdasar Time and Motion Study - Purwaningsih Purwaningsih; Nursalam Nursalam; Hanik Endang Nihayati; Yulis Setiya Dewi; Sudarsono Sudarsono (Universitas Airlangga, 2007)
The objective of this study was to analyze the relationship between working burden with time and motion study. The research’s design was used cross sectional studies with 56 samples of nurse which are taken by using purposive sampling technique. Data were collected for working burden by using observational with time and motion study, for nurses motivation and nursing care quality by using questioners with multiple choices. Data were analyzed by using Spearman’s Rho test with value level of p<0.05. The result showed that there were no relationship between working burden and nursing care quality with value level of p>0.05.